Localization of Maxillary Impacted Canine Using Cone Beam Computed Tomography for Assessmentof Angulation, Distance From Occlusal Plane, Alveolar Width and Proximity to Adjacent Teeth - Rahman, Vian Fouad; Fatah, Ahlam Ahmed (Journal of Baghdad College of Dentistry, 2017)
ABSTRACT Backgrounds: Maxillary canine impaction is complicated and time consuming to treat, for being highly diverse in inclination and location; it may be a companied by root resorption of the neighboring teeth. CBCT has been used for its’ diagnostic reliability in localization of impacted canine and revealing its’ serious local complications. Objectives: Localization of maxillary impacted canine using cone beam computed tomography for assessment of angulation, distance from occlusal plane, alveolar width and proximity to adjacent teeth. Subjects and Methods: The study sample was 33 subjects 16 females and 17 males attended to Al-Wasitti general hospital in Baghdad city-Oral and maxillofacial radiology department for CBCT scan investigationfrom November/2015 to April/2016. By using theCS 9000 device, 3D images and coronal, axial and sagittal views obtained to perform the selected measurements. Results: Contact of impacted canine to the nearby teeth had a strong effect on their root resorption. Vertical or horizontal angulation measurement in axial view, was not possible for a number of cases.Comparison of the angulation measurement validity between axial and coronal views, had showed an obvious statistical difference in coronal view for vertical angulation, and in the axial view for horizontal angulation calculation. Correlation of the canine localizations found in the study with the measurements, showed a significant statistical difference with age and vertical angulation (coronal view). Age or gender correlation with the measurements wasnon significant statistically, except for age with vertical angulation (coronal view). Conclusion: utilization of CBCT provides a worthy data about the impacted maxillary canine localization, for more explanation and treatment of these cases surgically and by orthodontics.